Hardware implementation for estimation of fasting blood glucose from saliva. (2023) - Nirmala, R.; Mathana, J.M.; AnneRamya, T.; Gomathi, R.
Abstract: Worldwide, people are facing diabetes which is characterized by high Fast Blood Glucose Level (FBGL) over a prolonged period of time. The main drawbacks of existing methods for estimation of FBGL are their high cost and invasive nature requiring frequent blood with-drawls. Hence, there is an unmet need to find an alternate method that can estimate blood glucose level conventionally, non-invasively and affordably. In the proposed work, an alternative method for estimating blood glucose based on variation in the electrochemical parameters of saliva is discussed. The role of saliva as a diagnostic tool is assessed by correlating fasting blood serum glucose and salivary glucose in the patient. The proposed system consists of sensor module, processor module, and IOT module. A proof of concept prototype is developed with integrated sensor for all the relevant parameters. PIC Microcontroller is the controlling unit of the whole system. The various sensors for measuring heart rate, temperature, pH and humidity are used in the work. This non-invasive blood glucose monitoring method is efficient and painless for FBGL estimation from saliva.